2019
DOI: 10.1021/acsabm.9b00420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver-Containing Titania Layers for Bioactivity, Antibacterial Activity, and Osteogenic Differentiation of Human Mesenchymal Stem Cells on Ti Metal

Abstract: Biomaterials with better osteogenic capacity, rapid osteo-integration, and higher mechanical strength are undoubtedly preferred for successful bone implant development. A porous sodium hydrogen titanate layer was formed on Ti metal by NaOH treatment, and the Na + ions were replaced by Ag + ions by subsequent AgNO 3 treatment that formed silver-containing hydrogen titanate. Heat treatment at 600 °C transformed sodium hydrogen titanate into sodium titanate with sheet-like morphology, whereas silver-containing hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Surprisingly, when Ca and Ag were co-decorated on the Ti–6Al–4V alloy surface, the bone-like apatite formation could be retained on its surface. From our previous studies and also from the present results, it can be seen that only Ag decorated surface formed anatase TiO 2 whereas rutile TiO 2 was dominant in the case of only Ca decorated Ti–6Al–4V alloy surface [ 32 , 33 ]. When it comes to the co-decoration of Ca and Ag, anatase TiO 2 peaks became more prominent.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Surprisingly, when Ca and Ag were co-decorated on the Ti–6Al–4V alloy surface, the bone-like apatite formation could be retained on its surface. From our previous studies and also from the present results, it can be seen that only Ag decorated surface formed anatase TiO 2 whereas rutile TiO 2 was dominant in the case of only Ca decorated Ti–6Al–4V alloy surface [ 32 , 33 ]. When it comes to the co-decoration of Ca and Ag, anatase TiO 2 peaks became more prominent.…”
Section: Resultssupporting
confidence: 74%
“…Among these, alkali-heat treatment is the most common and cost-effective as it induces faster bone-bonding ability, both in vitro and in vivo. [ 30 , 31 , 32 , 33 , 34 ] However, cytotoxicity caused by the Na + ion release from the alkali-heat treated Ti metal/Ti alloy surface can affect the surrounding cells. To address this, in our previous study, the Na + ions in the alkali-heat treated Ti metal was successfully replaced by Ca 2+ ions to improve bioactivity and attract more adhesion of bone cells on the implant surface [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samberg et al have reported no influence of Ag NPs on human adipose-derived stem cell differentiation [ 40 ]. Rajendran et al [ 41 ] have demonstrated the biocompatibility of Ag/TiO 2 anatase structures using MG-63 and MSCs and bactericidal activity against S. aureus . At the same time, a stimulating effect of silver on the osteogenic differentiation of MSCs was found.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the cells were washed with PBS and xed using 4% paraformaldehyde for 15 min. Immunostaining was carried out by incubating the cell-laden scaffolds and control cells with anti-αtubulin / anti-Vimentin antibodies at 4°C overnight, as described [25]. DAPI served as the nuclear stain in each.…”
Section: Assessment Of Cell Adhesion In Ltration and Growthmentioning
confidence: 99%